1993
DOI: 10.1007/bf01974313
|View full text |Cite
|
Sign up to set email alerts
|

Effects of leaf blast on growth and production of a rice crop

Abstract: Rice crops grown under irrigated conditions were inoculated with Pyricularia oryzae during early growth stages to study the effect of leaf blast on yield formation. The inoculations led to severe epidemics of leaf blast around maximum tillering, characterized by the presence of typical blast lesions and an accelerated senescence of heavily infested leaf tissue. Leaf blast led to a prolonged tillering and a delay in flowering and maturity.Crop growth rate and leaf area formation declined sharply during establis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
20
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 10 publications
5
20
0
Order By: Relevance
“…), suggesting that foliar fungi have greatest effects on their host plants at low plant diversity. The decline in foliar N in subplots where fungi were removed in the current experiment, particularly at low diversity, is consistent with past studies which have shown that foliar fungal diseases can cause N retention in diseased leaves (Bastiaans ; Garry et al . ; Gooding et al .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…), suggesting that foliar fungi have greatest effects on their host plants at low plant diversity. The decline in foliar N in subplots where fungi were removed in the current experiment, particularly at low diversity, is consistent with past studies which have shown that foliar fungal diseases can cause N retention in diseased leaves (Bastiaans ; Garry et al . ; Gooding et al .…”
Section: Discussionsupporting
confidence: 92%
“…For example, the severity of infection by species-specific foliar fungi declines with increasing plant diversity (Mitchell, Tilman & Groth 2002;Rottstock et al 2014), suggesting that foliar fungi have greatest effects on their host plants at low plant diversity. The decline in foliar N in subplots where fungi were removed in the current experiment, particularly at low diversity, is consistent with past studies which have shown that foliar fungal diseases can cause N retention in diseased leaves (Bastiaans 1993;Garry et al 1996;Gooding et al 2005). Taken together, these results suggest that the magnitude of the effect of foliar fungi on host foliar chemistry depends on the intensity of the fungal-host interaction.…”
Section: Discussionsupporting
confidence: 91%
“…The effects of diseases on crop growth and yield can be predicted by understanding the physiological changes in a pathogen's host during the infection process [30]. Photosynthesis is the key physiological process affected by foliar pathogens [14,31] and proper assessment of photosynthesis in plants infected by pathogens can provide crucial insight into the mechanisms underlying hostpathogen interactions [32].…”
Section: Introductionmentioning
confidence: 99%
“…At heading and during grain filling stages of the rice plant nitrogenous compounds may increase, decrease or cease, depending on the environmental conditions, cultivar, and/or nitrogen fertilizer rate of which may influence rice blast incidence (Wilson et al,1990;Norman et al, 1992). Bastiaans, (1993) reported that rice blast disease reduced nitrogen uptake before flowering and increased relative contribution of the stem to the overall nitrogen reallocation during the grain filling stage. Other studies by Koutroubas et al (2008) showed that when rice plant is inoculated with blast fungus, nitrogen utilization efficiency for both yield and biomass production was reduced.…”
Section: Nitrogenmentioning
confidence: 99%